Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Answer:6144
Step-by-step explanation:
If f(1)=6f(1)=6 and f(n)=4f(n-1)f(n)=4f(n−1) then find the value of f(6)f(6).
f(1)=
f(1)=
\,\,6
6
f(\color{darkgreen}{2})=
f(2)=
\,\,4f(\color{darkgreen}{2}-1)
4f(2−1)
=
=
\,\,4f(1)
4f(1)
=
=
\,\,4(6)
4(6)
Substitute f(1)=6
f(2)=
f(2)=
\,\,24
24
f(\color{darkgreen}{3})=
f(3)=
\,\,4f(\color{darkgreen}{3}-1)
4f(3−1)
=
=
\,\,4f(2)
4f(2)
=
=
\,\,4(24)
4(24)
Substitute f(2)=24
f(3)=
f(3)=
\,\,96
96
f(\color{darkgreen}{4})=
f(4)=
\,\,4f(\color{darkgreen}{4}-1)
4f(4−1)
=
=
\,\,4f(3)
4f(3)
=
=
\,\,4(96)
4(96)
Substitute f(3)=96
f(4)=
f(4)=
\,\,384
384
f(\color{darkgreen}{5})=
f(5)=
\,\,4f(\color{darkgreen}{5}-1)
4f(5−1)
=
=
\,\,4f(4)
4f(4)
=
=
\,\,4(384)
4(384)
Substitute f(4)=384
f(5)=
f(5)=
\,\,1536
1536
f(\color{darkgreen}{6})=
f(6)=
\,\,4f(\color{darkgreen}{6}-1)
4f(6−1)
=
=
\,\,4f(5)
4f(5)
=
=
\,\,4(1536)
4(1536)
Substitute f(5)=1536
f(6)=
f(6)=
\,\,6144
6144
\text{Geometric Sequence:}
Geometric Sequence:
Common ratio of 4
6,24,96,384,1536,6144, ...
6,24,96,384,1536,6144,...
\text{Final Answer:}
Final Answer:
6144
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.